Adherence to Antipsychotics among Patients with Schizophrenia at Selected Tertiary Level Hospitals - Yakha, Bhim Maya; Das, Dorwin; Tiwari, Suraj; Sharma, Pujan (Journal of Advanced Academic Research, 2024)
Background: Schizophrenia is a severe mental disorder where nonadherence is present in patients so that relapse, rehospitalization and treatment resistant can occur. Objectives: To identify the level of adherence to antipsychotics among patients with schizophrenia and to find its association with socio-demographic variables. Materials and method: A descriptive, cross-sectional study design was used for the study. 422 samples were collected using the purposive sampling technique Data was collected by the face-to-face interview technique during March, April, and May 2023. Questionnaire related to Socio-demographic information, standard valid tool Drug Attitude Inventory (DAI-10) was used as instrument. Data were analyzed using descriptive and inferential statistics with SPSS version 20. Results: The mean age of the respondents was 41.02, ±12.77. More than half52 (12.3%) of respondents were taking antipsychotics for more than 15 years. Majority of respondents 342 (81.0%) were taking atypical types of antipsychotics. Only 220 (52.1%) of respondents has moderate level of adherence towards antipsychotic medicine. Significant association was found between duration of illness and adherence level where p=0.006. There is mean difference found p=<0.001 from nonadherent group to moderate adherent and adherent group and from moderate adherent-to-adherent group. Conclusion: Nonadherence was found important factor low Quality of life among schizophrenia patient. Implementation of community mental health program is necessary to reduce treatment gap and decrease nonadherence. It is essential to improve adherence on antipsychotic for better quality of life among schizophrenia patient.